Obstacle-avoidance trajectory planning and sliding mode-based tracking control of an omnidirectional mobile robot - Sun, Zhe; Hu, Shujie; Miao, Xinan; Chen, Bo; Zheng, Jinchuan; Man, Zhihong; Wang, Tian (Frontiers in Control Engineering, 2023)
This paper proposes a trajectory-planning scheme and a trajectory-tracking control strategy for a Mecanum-wheeled omnidirectional mobile robot by using artificial potential field and discrete integral terminal sliding mode, respectively. First, a discrete kinematic-and-dynamic model is established for the omnidirectional mobile robot. Then, an obstacle-avoidance trajectory is planned and updated iteratively by utilizing artificial potential field functions. Afterward, a discrete integral terminal sliding mode control algorithm is designed for the omnidirectional mobile robot such that the robot can track the planned trajectory accurately. Meanwhile, the stability of the control system is proved in the sense of Lyapunov. Last, simulations are executed in the scenarios of static obstacles and dynamic obstacles. The simulation results demonstrate the effectiveness and merits of the presented methods.